SSCP typing of growth hormone gene and its association with birth weight in Black Bengal goat - DAYAL, SHANKER; KUMARI, RAJNI; CHAKRABARTI, ASIT; KUMAR, PANKAJ; SAHOO, SHREE PRASAD; KAUSHIK, PURUSHOTTAM; DEY, AMITAVA (The Indian Journal of Animal Sciences, 2014)
Growth hormone either directly or indirectly is the main regulator of postnatal somatic growth, stimulating anabolic process such as skeletal growth and protein synthesis and its deposition in tissues and organs. Therefore, genetic variation of growth hormone gene and its association with birth weight as an indicator of growth performance was investigated in Black Bengal goat. A 245 bp fragment (partial intron 1, exon 2 and partial intron 2) of growth hormone gene was analyzed for detection of polymorphism expected to be present at this locus. SSCP typing revealed 5 genotypes AA, AB, AC, AD and CC and consequently, 4 alleles A, B, C and D were identified. Least square analysis revealed that genotypes had significant effect on birth weight. Animals having AC genotype had highest birth weight whereas animals having CC genotype had lowest birth weight.